2024
DOI: 10.21203/rs.3.rs-3897762/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced stereodivergent evolution of carboxylesterase for efficient kinetic resolution of near-symmetric esters through machine learning

Guochao Xu,
Zhe Dou,
Xuanzao Chen
et al.

Abstract: Carboxylesterases serve as potent biocatalysts in the enantioselective synthesis of chiral carboxylic acids and esters. However, naturally occurring carboxylesterases exhibit limited enantioselectivity, particularly towards ethyl 3-cyclohexene-1-carboxylate (CHCE), due to its nearly symmetric structure. While machine learning has proven effective in expediting directed evolution, the lack of models for prediction of enantioselectivity for carboxylesterases has hindered progress, primarily due to challenges obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Another example is the recent pre-print by Xu et al, where the authors employ physicochemical properties such as volume, hydrophobicity, and π-π interactions to model and improve enantioselectivity of carboxylesterase AcEst1 from Acinetobacter sp. JNU9335 (Xu et al, 2024). Instead of manually choosing between the many similar indices, the inherent patterns of the physicochemical properties can be extracted through their principle components, such as the Vectors of Hydrophobic, Steric, and Electronic properties (VSHE) (Mei et al, 2005), zscales (Hellberg et al, 1987;Jonsson et al, 1989;Sandberg et al, 1998;Wold et al, 2011), the DL-based amino acid parameter representations by Meiler et al (Meiler et al, 2001), or the five factors described by Atchley et al (Atchley et al, 2005).…”
Section: Fixed Sequence Representationsmentioning
confidence: 99%
“…Another example is the recent pre-print by Xu et al, where the authors employ physicochemical properties such as volume, hydrophobicity, and π-π interactions to model and improve enantioselectivity of carboxylesterase AcEst1 from Acinetobacter sp. JNU9335 (Xu et al, 2024). Instead of manually choosing between the many similar indices, the inherent patterns of the physicochemical properties can be extracted through their principle components, such as the Vectors of Hydrophobic, Steric, and Electronic properties (VSHE) (Mei et al, 2005), zscales (Hellberg et al, 1987;Jonsson et al, 1989;Sandberg et al, 1998;Wold et al, 2011), the DL-based amino acid parameter representations by Meiler et al (Meiler et al, 2001), or the five factors described by Atchley et al (Atchley et al, 2005).…”
Section: Fixed Sequence Representationsmentioning
confidence: 99%
“…A variety of techniques, including error-prone PCR (epPCR), , saturation mutagenesis, and others, can be used to explore the vast sequence space and discover new biocatalysts. , Traditional directed evolution has been extensively used to improve the regioselectivity, diastereoselectivity, and enzyme activity. , (2) Recently, machine learning has emerged as a powerful tool to support directed evolution, enabling the exploration of larger sequence spaces (Figure c). Numerous studies have demonstrated the capacity of machine learning to predict sequence-activity (selectivity) relationships. While there has been considerable research in machine learning for protein engineering, the approach is seldom used to achieve stereodivergent synthesis and only a limited number of studies have compared directed evolution and machine-directed evolution. , …”
Section: Introductionmentioning
confidence: 99%